Pengaruh Curent Ratio dan Total Assets Turnover Terhadap Financial Distress Pada Sektor Transportasi dan Logistik yang Terdaftar di BEI 2017-2021 - Mela Apriyanti (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2023)
Financial distress can be interpreted as a decrease in the company’s financial condition before bankrupty. As a financial distress prediction model, this study aims to determine the effect of Liquidity (Curent Ratio) And Activity (Total Assets Turnover) on Financial Distress in the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2017-2021 period. The research method to be used in the study is Panel Data Regression Analysis use the Eviews program with a significance level of 5% . The results of this study shows that Liquidity (Curent Ratio) has no effect on Financial Distress, while Activity (Total Assets Turnover) has a negative effect on Financial Distress. But simultaneously, Liquidity (Curent Ratio) and Activity (Total Assets Turnover) have an effect on Financial Distress. This research indicates that that liquidity (current ratio) is not a factor that affects financial distress while activity (total assets turnover) is a factor that affects financial distress.Keywords : Activity; Curent Ratio; Financial Distress; Liquidity; Total Assets Turnover